Intellectual Capital Disclosure in Malaysian IPO Prospectuses : A Comparison between Financial Crisis-recovery and Post-crisis period - Alex, Andrea Sangeeta (2017)
As the importance of IC has grown over the past decade, this paper aims to investigate corporate governance characteristics, firm-specific characteristics and external influences on the extent of IC disclosure in Malaysian IPO prospectuses over the period of the financial crisis-recovery [2008-2011] and post-crisis [2012-2015] using multiple regression analysis. The study also looks at indirect and direct impact of ICD on level of underpricing. Content analysis of IPO prospectuses is used to investigate ICD in a sample of 106 organizations between 2008-2015 where disclosure was computed using disclosure index.From the investigation of corporate governance, firm characteristics and external influence it was found that none of the variables could be used as explanatory variable for ICD in both economic situations however, in crisis-recovery situation firm performance was found to be negatively significant with ICD whereas, in post-crisis period reporting accountant was found to be positively significant, furthermore, at (α<0.1) with foreign activity had negative association. In the case of underpricing although overall ICD was not significantly associated, individual variable of foreign activity was found to be positively significant in crisis-recovery and negatively significant in post-crisis. Some of the policy implications identified by this study is that ICD results tend to be inconclusive and inconsistent which perhaps is because of the absence of a reporting framework therefore regulators should implement guidelines for organizations to conveniently practice ICD. Furthermore, a practical implication is focused on younger organizations tend to disclose more IC hence, the government can encourage this by providing tax exemptions or other subsidies to ease burden of costs of disclosure. This study adds originality as it investigates a new avenue in the literature of ICD which is association between government pressure and ICD in the context of Malaysian IPO prospectuses, although there was no significant association this can encourage further research into this area to reduce literature gap in ICD. And also, the comparison of ICD over different economic situations might give insight for government institutions and regulatory bodies on how to promote IC based activities and in turn increas ICD.